2014
DOI: 10.1007/s10072-014-1769-6
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in cluster headache: four cases and review of the literature

Abstract: Although cluster headache (CH) is the most disabling form of primary headache, little evidences regarding alternative and complementary therapies are available. Only few dated studies and some isolated cases are described. We describe four patients with CH treated with acupuncture as a preventive treatment, combined with verapamil or alone. All patients received acupuncture treatment twice/week for 2 weeks, then once/week for 8 weeks, and then once/alternate weeks for 2 weeks. According to Traditional Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hegu (LI 4) (9 studies) ( Zeng et al, 2006 ; Dougherty et al, 2008 ; Kong et al, 2009a , b ; Zyloney et al, 2010 ; Jiang et al, 2014 ; Theysohn et al, 2014 ; Lee et al, 2015 ; Niu et al, 2017 , Zusanli (ST 36) (8 studies) ( Weiting et al, 2003 ; Zhang et al, 2003a , b ; LaMei et al, 2013a , b ; Theysohn et al, 2014 ; Lin et al, 2018 ; Wenjin et al, 2020 , and Sanyinjiao (SP 6) (4 studies) ( Weiting et al, 2003 ; Zhang et al, 2003a , b ; Cao et al, 2019 ( Supplementary Table 4 ) were the most used acupoint selection in these 27 studies. The aforementioned acupoints were widely used for pain relief in the clinic ( Zeng et al, 2009 ; Fofi et al, 2014 ; Wang et al, 2015 . Besides, the acupoints were located on the four limbs which were commonly used because they were easy to perform acupuncture manipulation during the scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Hegu (LI 4) (9 studies) ( Zeng et al, 2006 ; Dougherty et al, 2008 ; Kong et al, 2009a , b ; Zyloney et al, 2010 ; Jiang et al, 2014 ; Theysohn et al, 2014 ; Lee et al, 2015 ; Niu et al, 2017 , Zusanli (ST 36) (8 studies) ( Weiting et al, 2003 ; Zhang et al, 2003a , b ; LaMei et al, 2013a , b ; Theysohn et al, 2014 ; Lin et al, 2018 ; Wenjin et al, 2020 , and Sanyinjiao (SP 6) (4 studies) ( Weiting et al, 2003 ; Zhang et al, 2003a , b ; Cao et al, 2019 ( Supplementary Table 4 ) were the most used acupoint selection in these 27 studies. The aforementioned acupoints were widely used for pain relief in the clinic ( Zeng et al, 2009 ; Fofi et al, 2014 ; Wang et al, 2015 . Besides, the acupoints were located on the four limbs which were commonly used because they were easy to perform acupuncture manipulation during the scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is one of the most well-known alternative therapy. Fofi et al showed some significant improvement in acupuncture for cluster headache [4]. Although Cochrane review and United Kingdom National Institute for Health and Care Excellence recommend acupuncture as a prophylactic treatment for migraine and tension headache, the effectiveness for cluster headache remains unclear [5].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is a traditional Chinese medical therapy that involves the stimulation of acupuncture points on the patient's body, usually by the insertion of fine, disposable needles [ 9 ]. It is among the most widely used complementary treatments for chronic pain, including headaches [ 10 ]. Acupuncture has been found to effectively reduce the frequency and severity of migraine and tension headache attacks [ 11 ].…”
Section: Introductionmentioning
confidence: 99%